Requirement for ER-mitochondria Ca2+ transfer, ROS production and mPTP formation in L-asparaginase-induced apoptosis of acute lymphoblastic leukemia cells - Lee, Jung Kwon; Rosales, Jesusa L.; Lee, Ki-Young (Frontiers in Cell and Developmental Biology, 2023)
Acute lymphoblastic leukemia (aLL) is a malignant cancer in the blood and bone marrow characterized by rapid expansion of lymphoblasts. It is a common pediatric cancer and the principal basis of cancer death in children. Previously, we reported that L-asparaginase, a key component of aLL chemotherapy, causes IP3R-mediated ER Ca2+ release, which contributes to a fatal rise in [Ca2+]cyt, eliciting aLL cell apoptosis via upregulation of the Ca2+-regulated caspase pathway (Blood, 133, 2222–2232). However, the cellular events leading to the rise in [Ca2+]cyt following L-asparaginase-induced ER Ca2+ release remain obscure. Here, we show that in aLL cells, L-asparaginase causes mitochondrial permeability transition pore (mPTP) formation that is dependent on IP3R-mediated ER Ca2+ release. This is substantiated by the lack of L-asparaginase-induced ER Ca2+ release and loss of mPTP formation in cells depleted of HAP1, a key component of the functional IP3R/HAP1/Htt ER Ca2+ channel. L-asparaginase induces ER Ca2+ transfer into mitochondria, which evokes an increase in reactive oxygen species (ROS) level. L-asparaginase-induced rise in mitochondrial Ca2+ and ROS production cause mPTP formation that then leads to an increase in [Ca2+]cyt. Such rise in [Ca2+]cyt is inhibited by Ruthenium red (RuR), an inhibitor of the mitochondrial calcium uniporter (MCU) that is required for mitochondrial Ca2+ uptake, and cyclosporine A (CsA), an mPTP inhibitor. Blocking ER-mitochondria Ca2+ transfer, mitochondrial ROS production, and/or mPTP formation inhibit L-asparaginase-induced apoptosis. Taken together, these findings fill in the gaps in our understanding of the Ca2+-mediated mechanisms behind L-asparaginase-induced apoptosis in aLL cells.